Structural Evaluation of Timber-Concrete Composite Floor Constructed Using Open Web Truss Joist Made of LVL Paraserianthes falcataria - Awaludin, Ali; Wusqo, Urwatul; Rusgiyanto, (International Journal of Integrated Engineering, 2024)
The adoption of LVL (laminated veneer lumber) technology is significantly improving the potential application of Sengon wood species as structural components in buildings. Therefore, this study aimed to construct two timber-concrete composite floors using open web truss joist (OWTJ) made from LVL Sengon and a 60-mm thick of concrete slab, along with a timber floor without concrete for comparison. All floors shared a common dimension, measuring 6460 mm length, and 1000 mm in width. The non-composite (floor A) had a depth of 600 mm, while floors B and C had 660 mm, including 60-mm thick of concrete slab. In floor B, slab above OWTJ was constructed with cast-in-situ concrete, whille C was prefabricated and connected through 5/16 inch-diameter screws. All floors were subjected to a distributed water loading to 300 mm height, while floor A passed through creep test for a duration of 14 days. The results showed that floor deflection of all specimens was less than the allowable limits required by the design standards (1/360 of the floor length). Floor B yielded the smallest deflection at 3.82 mm, which was slightly higher compared to the predictid value by the numerical model (3.67 mm). Actual strain measurement through strain-gauge at some locations of floor B verified by the numerical model showed that both concrete slab and members of OWTJ were stressed below the maximum stresses. The results positively supported the new application area of LVL made from Sengon wood species in structural components, particularly as open web truss joist of TCC floor system